Hybrid plasma enhanced chemical vapour deposition/sputtering system for preparation of luminescent silicon carbon films / Nur Maisarah binti Abdul Rashid - Abdul Rashid, Nur Maisarah (2013)
Radio frequency plasma enhanced chemical vapour deposition (r.f PECVD) process is a well-established technique for depositing amorphous silicon carbon (a-SiC) films. However, an environmental friendly deposition technique which does not involve the use of toxic gas, silane (SiH4) is a much preferred technique. In this work a hybrid r.f. PECVD/sputtering system was designed for this purpose. This system combines the use of radio frequency (r.f.) reactive sputtering with r.f. PECVD for the growth of amorphous a-SiC films. The use of amorphous silicon (a-Si) target as a sputtering source eliminates the use of SiH4 as Si source for the films. This work is divided into three parts consisting of studying (i) film deposited by r.f. PECVD through discharge of hydrogen (H2) diluted methane (CH4) with different total gas pressure; (ii) films deposited by sputtering of a-Si target at different Argon (Ar) flow rate; and (iii) films deposited by the hybrid r.f. PECVD/sputtering system from CH4 discharge and sputtering of a-Si target at different r.f. power with a fixed Ar to CH4 ratio of 7.5:1. In the first part, the effect of total gas pressure on the film properties were studied with CH4 to H2 flow rate ratio fixed at 1:5. The effects of Ar flow rate of 5.7, 7.5, 15.0 and 30.0 sccm on the properties of the films were studied in the second part of the work. The last part of the work involved the study of the effect of r.f. power of 60, 80, 100, 120 and 150 W on the film properties. Raman, Fourier transform infrared, Auger electron and photoluminescence emission spectroscopies were used to analyze the properties of the films. Film thickness was measured using mechanical profilometer to study the film growth rate. It is established from the results that the films deposited by hybrid r.f. PECVD/sputtering system are multiphase in structure which consist of a-Si, a-SiC, a-C:H and SiOx phases. The origin of PL emission in the films is mainly through recombination processes in the sp2-C clusters embedded within the a-C:H and SiOx phases in the film structure